The role of asymmetric information in multi-peril picture-based crop insurance: Field experiments in India - Ceballos, Francisco; Kramer, Berber (International Food Policy Research Institute, 2021)
Smallholder farmers in developing countries generally lack access to affordable agricultural insurance, in part because of high loss verification costs and asymmetric information in indemnity insurance and basis risk in index-based insurance. Advances in remote sensing and other digital technologies can help overcome these challenges by allowing for low-cost, remote loss verification, and settling claims based on observed visible damage in a farmer’s fields. By effectively proxying for indemnity insurance, however, such a product may be subject to moral hazard and adverse selection. We test these hypotheses leveraging the rollout of picture-based crop insurance among smallholder farmers in northwestern India. We find no evidence of moral hazard or adverse selection, and that the use of technologies increases willingness to pay. We conclude that digital technologies are a valuable tool to provide low cost, sustainable crop insurance remotely, at lower levels of basis risk than index products.